University archives both old and new: the case of New York University, and its campuses in New York and Abu Dhabi. Issue 1 (January 2020) - Bauer, Brad; Bunde, Janet
Abstract : The nature and role of university archives, as well as the archival profession in general, have evolved rapidly over the past several decades. Two archival repositories within New York University vividly illustrate some of these changes: the university archives of its flagship campus in New York, and that of its recently established campus in Abu Dhabi. When looked at not only in comparison with one another, but also within the larger context of the evolution of archival appraisal theory, one can see reflected both the development of the profession in the United States during the twentieth century, and some of the present-day challenges faced by university archivists as they grapple with changes in the nature and form of the historical record.